TUGAS PRARANCANGAN PABRIK NITROGLISERIN DARI GLISERIN DAN CAMPURAN ASAM KAPASITAS 20.000 TON/TAHUN - , PUTRA ADIE KUSUMA, Dr. Ir. Sarto., M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Nitroglycerin plant from Glycerol and mixed acid is designed to operate continuously for 24 hours/day during 330 days/year. It has capacity of 20,000 tons/ year. The reaction occurs in the isotherm process in flow stirred tank reactor that operates at a pressure of 1 atm and temperature of 20oC. The reactionâs type is exothermic. Regarding to the fact, the process need brine cooling liquid (CaCl2 25%) which flow through coil. Plantation of 20,000 tons/year nitroglycerin is required 8.255,44 tons/year of glycerol 98,5%, 27.374 tons/year of nitric acid 68%, 133,6 tons/year of sulfuric acid 98%, 3.179,43 tons/year of Na2CO3 and 4.1667 tons/year of ethanol. Utility components are 126.118,7 liters/year of water, 4.773,45 liters/year of fuel, 65.795 m3/year of CaCl2 brine, 270,8 kVA/year of electricity, and 792.000 m3(STP condition) per year. Planned factory will be established in Bekasi, West Java in the land area of 20.000 m2 including area for expansion. From the economic evaluation, we obtained the results: fixed capital of Rp65.651.381.878,61 + US$3.678.794,05, working capital of Rp15.335.561.172,25 + US$1.496.297,81. Return of Investment before Tax = 28,33% , Return of Investment after Tax = 14,16% , Pay Out Time before Tax =2,61 years, Pay Out Time after Tax = 4,14 years, Break Even Point = 40,57% , Shut Down Point = 13,3%, and Discounted Cash Flow Rate of Return = DCFRR = 18,67 %. From the results of economic evaluation, we may conclude that the nitroglycerin plant with capacity of 20.000 tons/ year is quite interesting for further study.